2012
DOI: 10.3892/etm.2012.499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apelin and leptin on renal functions following renal ischemia/reperfusion: An experimental study

Abstract: The present study aimed to investigate the effects of apelin and leptin on renal functions following renal ischemia/reperfusion (I/R). A total of 32 rats were divided into four groups. The control group was not induced with ischemia, but was administered normal saline intraperitoneally. Normal saline, apelin and leptin were administered intraperitoneally to the I/R, ischemia/reperfusion and apelin (I/R+A) and ischemia/reperfusion and leptin (I/R+L) groups, in turn for three days prior to the surgical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…When ischemia persists for a certain duration, following which perfusion recovers, organizational structural and functional recovery may be impaired and kidney dysfunction and structural damage may be aggravated, which is known as IRI (28). Following shock, heart failure, cardiopulmonary bypass or kidney transplantation, IRI usually affects the treatment outcome, particularly in kidney transplant recipients, in which IRI is one of the causes of surgical failure.…”
Section: Discussionmentioning
confidence: 99%
“…When ischemia persists for a certain duration, following which perfusion recovers, organizational structural and functional recovery may be impaired and kidney dysfunction and structural damage may be aggravated, which is known as IRI (28). Following shock, heart failure, cardiopulmonary bypass or kidney transplantation, IRI usually affects the treatment outcome, particularly in kidney transplant recipients, in which IRI is one of the causes of surgical failure.…”
Section: Discussionmentioning
confidence: 99%
“…46 Renal I/R injury usually causes primary tubular epithelial cell injury, in-47 cluding tubular obstruction and reduced tubular re-absorption of NaCl. 48 However, several studies reported that hemodynamic changes induced 49 by renal I/R injury also occur, which lead to mesangial contraction and 50 cessation of glomerular filtration. Thus, the interaction of microvascular 51 (including glomerular and medullary parts) and tubular events both 52 contribute to the pathogenesis of acute ischemic renal failure [4,5].…”
mentioning
confidence: 97%
“…Apelins and APJ are widely expressed in animal and human heart, lung, kidney, brain, liver, breast, and skeletal muscle and abundantly found in cardiovascular, brain, lung, and breast cancers. Previous studies have shown that apelin/APJ system has effects on the function of cardiovascular system [4], has the functional and histopathological protective effects against renal ischemia/ reperfusion injury [5], and has the effect of analgesia [6]. In addition, apelin/APJ system is involved in many processes such as regulation of the release of hormone and metabolism [7], regulation of cell proliferation, migration, and apoptosis [8], and reduction of pulmonary inflammation and fibrin deposition [9].…”
Section: Introductionmentioning
confidence: 99%